2023
DOI: 10.1002/adfm.202305683
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Solvation Structure and Electrolyte Interface through Carbonyl Chemistry for Durable and Dendrite‐Free Zn Anode

Abstract: Aqueous Zn ion batteries are appealing systems owing to their safety, low cost, and environmental friendliness; however, their practical applicability is impeded by the growth of Zn dendrites and side reactions. Herein, a dual‐functional electrolyte additive, namely acetylacetone (AT) is utilized for the simultaneous regulation of the solventized structure and anode–electrolyte interface (AEI) to achieve a durable, dendrite‐free Zn anode. Theoretical calculations and experimental characterizations reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…With the import of l -Aa, the cycling life of Zn//Zn symmetric cells at high current density achieves a larger improvement compared with previous results with different additives. 13,14,28,34,54,57–64 The findings presented herein provide compelling evidence that the incorporation of l -Aa can yield a substantial development in the electrochemical reversibility of Zn anodes.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…With the import of l -Aa, the cycling life of Zn//Zn symmetric cells at high current density achieves a larger improvement compared with previous results with different additives. 13,14,28,34,54,57–64 The findings presented herein provide compelling evidence that the incorporation of l -Aa can yield a substantial development in the electrochemical reversibility of Zn anodes.…”
Section: Resultsmentioning
confidence: 65%
“…Among these strategies, electrolyte additives feature low cost and high operability and have drawn much attention in recent years, 31–33 which have a crucial effect on regulating the zinc coordination chemistry and are deemed as an effective pathway to attain superior performance ZIBs. The reported working mechanisms of electrolyte additives mainly include constructing water-poor interface, 34,35 reducing solvation effect, 36,37 and forming solid electrolyte interface. 38,39 Recently, various organic solvents were employed as the electrolyte additives to suppress the decomposition of H 2 O molecules and broaden the operational temperature range via the stronger interaction between H 2 O and the polar functional groups of the organic solvents, such as ethylene glycol, 40 dimethyl sulfoxide, 41 and methanol.…”
Section: Introductionmentioning
confidence: 99%
“…[36] The obtained results suggested that the sulfate group in (OSO 3 R) − with a certain electron-donating capability can coordinate with Zn 2+ , which is able to compete with the bound D 2 O molecules and tip the hydrated solvation balance of Zn 2+ . [37] In contrast, a negligible shift (4.717 ppm) of the 1 H peak can be observed after dissolving the SDS into the pure D 2 O, implying a weak interaction between the SDS and water molecules.…”
Section: Resultsmentioning
confidence: 97%
“…As previous studies have reported, the size of nucleated particles could become smaller when the nucleation overpotential increases, and the fine-grained nucleation facilitates the homogeneous Zn deposition, indicating that the deposition behavior can be optimized by the APM. 26,39,40 Meanwhile, the morphology of Zn deposited on the Cu metal in different electrolytes were observed to further investigate the influence of the H 2 O-poor EDL, and the digital photograph shows that the nucleation and growth of Zn is mainly in the local area of the Cu surface in 2 M ZnSO 4 ; the deposition morphology has no obvious improvement in 2 M ZnSO 4 + 0.1 mM APM (Fig. S12a and b, ESI†).…”
Section: Resultsmentioning
confidence: 99%